2018
DOI: 10.1002/jum.14894
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Bones: Assessing Whether Ultrasound‐Aided Instruction and Practice Improve Unassisted Soft Tissue Palpation Skills of First‐Year Medical Students

Abstract: Objectives Our purpose was to determine whether ultrasound (US)‐aided instruction and practice on musculoskeletal anatomy would improve first‐year medical students’ ability to locate and identify specific soft tissue structures by unaided palpation in the upper and lower extremities of healthy human models. Methods This study was a randomized crossover design with 49 first‐year medical students randomly assigned to 1 of 2 groups. Each group was provided expert instruction and hands‐on practice using US to scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…For each group of participants, before the course started, a scoring assessment of the participants' palpation skills in terms of accuracy and time was conducted with reference to previous studies 18 . In summary, the scoring test comprised an assessment of the accuracy and time required to palpate five tissues randomly selected for palpation by each participant from 30 tissues around the shoulder joint.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For each group of participants, before the course started, a scoring assessment of the participants' palpation skills in terms of accuracy and time was conducted with reference to previous studies 18 . In summary, the scoring test comprised an assessment of the accuracy and time required to palpate five tissues randomly selected for palpation by each participant from 30 tissues around the shoulder joint.…”
Section: Methodsmentioning
confidence: 99%
“…Many preliminary studies have reported improvements in palpation skills using US imaging 5 , 6 , 10 12 , 16 18 . However, most of these were observational studies that did not examine confounders or interventional studies without a control group.…”
Section: Introductionmentioning
confidence: 99%
“…For each group of participants, before the course started, a scoring assessment of the participants' palpation skills in terms of accuracy and time was conducted with reference to previous studies 14 . In summary, the scoring test comprised an assessment of the accuracy and time required to palpate ve tissues randomly selected for palpation by each participant from 30 tissues around the shoulder joint.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, systematic learning courses for improving palpation skills using US images have been developed to take advantage of the US images recently 10 . There has also been an increasing number of interventional studies on the usefulness of US imaging as a tool to improve the palpation skills of medical students or residents [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…In learning to perform physical examinations of the musculoskeletal system, Walrod et al [ 27 ] demonstrated that ultrasonography appeared effective in helping students locate and identify soft tissue structures on palpation compared to bony structures. Subsequent research conducted by the same group has suggested that ultrasound assistance might improve students’ abilities to correctly locate, palpate, and identify soft tissue structures in the limbs, provided they be allowed sufficient hands-on practice [ 28 ]. Ruiz-Curiel et al [ 29 ] showed that medical students’ skills in detecting joint inflammation on palpation significantly improved when using ultrasonography as an educational tool for feedback through a five-session training program over 13 weeks.…”
Section: Ultrasound As a Tool For Learning Basic Sciences And Physical Examination Skillsmentioning
confidence: 99%